2014
DOI: 10.3126/ijasbt.v2i4.11302
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Snake Gourd (Trichasanthes Anguina L) Test Hybrids Comparing with Four Popular Checks

Abstract: An experiment was conducted at Research and Development (Vegetable) Farm, Supreme Seed Company Limited, Mymensingh in 20th March to 14th June, 2013 to evaluate performance of eight snake gourd genotypes. Among snake gourd genotypes four were test hybrid viz. SG1001, SG1002, SG1003 and SG1004 (from the seven inbreed lines) and four were checks (three from local market and one from BADC) viz. SUPREMA, RUNNER, SURMA, ZUM LONG. Wide ranges of variability were found in the studied characters among the genotypes. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
7
3
0
Order By: Relevance
“…Single fruit weight (0.834), number of fruits per plant (0.646) and days to first harvest (0.347) showed direct positive effect on fruit yield per plant. This is in concordance with the results of Haque et al (2014) who found that fruit weight and number of fruits per plant had positive direct effect on fruit yield and Anandakumar et al(2017) who found that fruit yield showed significant positive phenotypic and genotypic correlation with number of fruits per plant in snake gourd. Node order of first female flower (-0.241), days to first male flowering (-0.095), days to first female flowering (-0.013) showed negative direct effect on yield of fruit.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Single fruit weight (0.834), number of fruits per plant (0.646) and days to first harvest (0.347) showed direct positive effect on fruit yield per plant. This is in concordance with the results of Haque et al (2014) who found that fruit weight and number of fruits per plant had positive direct effect on fruit yield and Anandakumar et al(2017) who found that fruit yield showed significant positive phenotypic and genotypic correlation with number of fruits per plant in snake gourd. Node order of first female flower (-0.241), days to first male flowering (-0.095), days to first female flowering (-0.013) showed negative direct effect on yield of fruit.…”
Section: Resultssupporting
confidence: 91%
“…Since some of these characteristics are significantly connected with one another and with yield, breeders constantly seek for evolutionary divergence among the traits to select desired types. Analyzing the relationships between these traits and how they relate to yield is essential when determining genotype selection (Singh, 2000).The majority of correlation coefficients at genotypic level were considerably larger than their corresponding correlation coefficients at phenotypic level, revealing that the environment had a masking effect that altered character expression while repressing phenotypic expression (Haque et al, 2014;Gurve et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The findings were in accordance with earlier reports by Triveni et al, [6] in ridge gourd. The findings were in accordance with earlier reports of cucurbits by Haque et al, [9] in snake gourd.…”
Section: Number Fruits Per Plantsupporting
confidence: 94%
“…Among the different varieties maximum Total Soluble Solid (43.14°Brix) was observed with AVT-2/2020/SPGVAR-5 and minimum Total Soluble Solid (1.50°Brix) was observed AVT-2/2020/SPGVAR-3 [11][12][13][14][15]. Among the different varieties maximum Ascorbic acid content (11.55 mg/100g) was observed with AVT-2/2020/SPGVAR-5 and minimum Ascorbic acid content (7.66 mg/100g) was observed AVT-2/2020/SPGVAR-3 [16][17][18][19][20].…”
Section: Tss [°Brix] and Vitamin C Content (Mg/100g)mentioning
confidence: 99%